A Case of Occlusal Reconstruction for Severe Attrition - Ueda, Takayuki (Nihon Hotetsu Shika Gakkai Zasshi, 2006)
Patient: A 57-year-old female complained of aesthetic disturbance, dysmasesis and phonation disorder by attrition. She had severe attrition of almost teeth. To avoid metal color exposure and attrition of opposing teeth, hybrid ceramics were used for veneered crowns and fixed partial denture. Since the prosthetic treatment, the patient wears a night guard to prevent attrition of her teeth and prosthesis. Discussion: There has been no specific trouble during the 4-year follow-up. Conclusion: It is considered that using hybrid ceramics for veneering crowns and fixed partial denture and night guard help to prevent the attrition of opposing teeth and abrasion of prosthesis.